Does birth season correlate with childhood stunting? An input for astrological nutrition - Melese Linger Endalifer; Gedefaw Diress; Bedilu Linger Endalifer; Birhanu Wagaye; Hunegnaw Almaw (BMC Pediatrics, 2022)
Abstract Introduction Chronic malnutrition is highly prevalent in Sub-Saharan Africa and a severe public health problem in Ethiopia.At country level in the past three decades,the prevalence of stunting is above 40%.Different researchs and intervention were implemented in the past;but the progresss is non-remarkable.Despite; the effect of birth season on childhood chronic malnutrition was not studied yet in Ethiopia. Methods This research was extracted from the 2016 demographic health survey of Ethiopia. The data was collected based on national and international scientific protocols. A total of 645 enumeration areas were selected for the national survey.The surevey uses two stage stratified sampling technique to gather data from the sampling unit. After excluding non eligible children a total of 8855 participants were included for final analysis.Height and weight were measured based on the standards nutritional assessment procedure.SPSS version 20 was used to analyze the data.Descriptive statistics were used to present the data. Binary and multivariable logistic regression models were regressed to identify the potential predictors.A p-value of less than 0.05 with 95% CI were used to declare an association. Result The prevalence of stunting in Ethiopia was 38.7% (95% CI: 36.8, 40.6). Season of birth had a significant association with stunting. The odds of being stunted among children born in the spring season were decreased by 16% as compared to children born in the winter season. Conclusion Children born in the spring season were less likely to be stunted (the so called October effect). The clear scientific relation between the season of birth and child anthropometric indicator is not well understood. Nutritional interventions and policies are better to consider the birth season of the child.